2020
DOI: 10.3390/math8040639
|View full text |Cite
|
Sign up to set email alerts
|

Fibonacci Numbers with a Prescribed Block of Digits

Abstract: In this paper, we prove that F 22 = 17711 is the largest Fibonacci number whose decimal expansion is of the form a b … b c … c . The proof uses lower bounds for linear forms in three logarithms of algebraic numbers and some tools from Diophantine approximation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…[1], the second author considered all Padovan numbers that can be written as a concatenation of two distinct repdigits and showed that the largest such number is P 21 = 200. More specifically, it was shown that if P n is a solution of the Diophantine equation Other related interesting results in this research direction include: the result of Bednařík and Trojovská [3], the result of Boussayoud, et al [4], the result of Bravo and Luca [5], the result of the second author [7], the result of Erduvan and Keskin [11], the result of Rayaguru and Panda [16], the results of Trojovský [17,18], and the result of Qu and Zeng [15]. A natural continuation of the result in Ref.…”
Section: }mentioning
confidence: 95%
“…[1], the second author considered all Padovan numbers that can be written as a concatenation of two distinct repdigits and showed that the largest such number is P 21 = 200. More specifically, it was shown that if P n is a solution of the Diophantine equation Other related interesting results in this research direction include: the result of Bednařík and Trojovská [3], the result of Boussayoud, et al [4], the result of Bravo and Luca [5], the result of the second author [7], the result of Erduvan and Keskin [11], the result of Rayaguru and Panda [16], the results of Trojovský [17,18], and the result of Qu and Zeng [15]. A natural continuation of the result in Ref.…”
Section: }mentioning
confidence: 95%
“…This paper is inspired by the results of Alahmadi et al [ 1 ], in which they show that the only Fibonacci numbers that are concatenations of two repdigits are , and Rayaguru and Panda [ 10 ], who showed that is the only balancing number that can be written as a concatenation of two repdigits. Other related interesting results in this direction include: the result of Bravo and Luca [ 3 ], the result of Trojovský [ 11 ], the result of Qu and Zeng [ 9 ], and the result of Boussayoud et al [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2011, F. Luca and R. Oyono [2] concluded that there is no solution (m, n, s) to the Diophantine equation F s m + F s m+1 = F n for integers m ≥ 2, n ≥ 1, s ≥ 3 by applying linear form in logarithms. There are many papers in the literature which solve Diophantine equations related to Fibonacci numbers and Lucas numbers [3][4][5][6][7][8][9][10][11][12][13][14]. In 2013, D. Marques and A. Togbé [3] found all solutions (n, a, b, c) to the Diophantine equation F n = 2 a + 3 b + 5 c and L n = 2 a + 3 b + 5 c for integers n, a, b, c with 0 ≤ max{a, b} ≤ c. In 2019, B. D. Bitim [4] investigated the solutions (n, m, a) to the Diophantine equation L n − L m = 2 • 3 a for nonnegative integers n, m, a with n > m. Let p be a prime number and max{a, b} ≥ 2, in 2009, F. Luca and P. Stǎnicǎ [5] concluded that there are only finitely many positive integer solutions (n, p, a, b) to the Diophantine equation…”
Section: Introductionmentioning
confidence: 99%